2013
DOI: 10.1186/1756-0500-6-271
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sexual violence and human immunodeficiency virus (HIV) infection among women using voluntary counseling and testing services in South Wollo Zone, Ethiopia

Abstract: BackgroundGender based violence affects the health and wellbeing of women across the world on an epidemic scale. While women remain more vulnerable to both sexual violence and risk of HIV infection, they are less able to access health and other welfare services than men. These vulnerabilities are further compounded by social factors, including the low status of women in many communities and their lack of decision-making power, both within the household and in wider society. The objective of this study was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…Sexual violence was also found to be higher in other studies conducted in different parts of the country. The difference from the current study ranges from 26.7% to 52% as compared to studies conducted in East Wollega [20], rural Ethiopia [31] Kersa district of Jimma Zone [29], South Wollo [32], Awi Zone [30] and Wolaita Sodo University [33]. The prevalence of IPV reported from these studies reflect the magnitude of the problem in specific regions of the country.…”
Section: Discussioncontrasting
confidence: 62%
“…Sexual violence was also found to be higher in other studies conducted in different parts of the country. The difference from the current study ranges from 26.7% to 52% as compared to studies conducted in East Wollega [20], rural Ethiopia [31] Kersa district of Jimma Zone [29], South Wollo [32], Awi Zone [30] and Wolaita Sodo University [33]. The prevalence of IPV reported from these studies reflect the magnitude of the problem in specific regions of the country.…”
Section: Discussioncontrasting
confidence: 62%
“…In the face of high gender inequalities, IPV poses an increased burden on women's health in Ethiopia. Although the consequences are underexamined in this country, some existing evidence shows its potential for producing severe physical, emotional, and reproductive health problems [7][8][9][10]. Severe consequences of IPV include reduced maternal health care utilization and adverse child health outcomes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The existing evidence regarding the effects of IPV on women’s health in Ethiopia is also limited. Existing studies have found associations between IPV and depression [ 28 31 ], psychiatric disorders [ 32 ], risk of acquiring sexually transmitted infections [ 27 ] and Human Immunodeficiency Virus (HIV) [ 33 , 34 ], unmet need for family planning [ 35 ], unintended pregnancy [ 27 ], and low maternal health service utilization [ 36 , 37 ]. Most of the studies have been conducted in small geographic locations that lack national level representativeness.…”
Section: Introductionmentioning
confidence: 99%